College students’ knowledge, attitudes, and practices of garbage sorting and their associations: a cross-sectional study of several universities in Beijing, China - Liu, Siyuan; Liu, Xiong; Li, Yibo; Yang, Dongli; Li, Feng; Yang, Junling (Frontiers in Public Health, 2024)
Background In recent years, the Chinese government has placed growing emphasis on environmental development. The implementation of effective waste separation practices in schools is crucial for establishing an ecological civilization in China. Objective The present study aimed to assess the knowledge, attitude, and practice (KAP) of waste separation among Chinese university students and to understand the demographic factors influencing the KAP of the interviewed students. These sociodemographic factors include gender, age, education, and family environment. Methods Based on the KAP theoretical model and the Lewin behavioral model (LBM), this study developed its questionnaire on college students’ KAP of rubbish sorting. A survey was conducted on 1,282 college students from five colleges and universities in Beijing. A one-way ANOVA, Pearson’s correlation analysis, and multiple linear stepwise regression analyzes were employed to explore the factors influencing college students’ KAP scores on waste sorting. The questionnaire’s reliability and validity were effectively verified through two rounds of Delphi expert consultation. Results The scores for KAP dimensions were 55.64, 69.18, and 54.8%, respectively. The overall KAP score of university students in waste classification was 46.93 ± 9.93, with a percentage score of 62.57%. More than half of the college students lack a clear understanding of waste classification. Grade, gender, major, highest family education, and family economic status all influence college students’ KAP scores on waste classification. There is a notable deficiency in school education regarding waste classification, with only 30.7% reporting having received such education. Conclusion This study unveils the overall KAP score of waste separation among Chinese college students, which is marginally acceptable. The interviewed students exhibit a positive attitude and a willingness to participate in waste separation. However, there is room for improvement in both knowledge and practices. A lack of knowledge about waste sorting emerges as the primary influence on individual-level practices. Consideration should be given to enhancing education and management of waste separation among college students, emphasizing the cultivation of an eco-conscious culture, and guiding students to establish correct ecological values.